ANALISIS NETWORK GATEKEEPING LIPUTAN PERJUANGAN GERAKAN MASYARAKAT ADAT: STUDI KASUS PADA BERITA LINGKUNGAN ONLINE MONGABAY - Sigit, Ridzki Rinanto; Rubiyanto; Suskarwati, Sri Ulya; Verselita, Akita Arum (JURNAL SIGNAL, 2023)
Sympathy for the struggle of indigenous peoples in the media is currently increasingly present with their sociological position as forest and climate guardians whose existence is increasingly fading along with the loss of their natural resources. This research identifies and analyzes editorial activities in reporting on indigenous people's struggles, referring to gatekeeping practices related to routine news production. This qualitative research uses case studies by analyzing relevant news texts created by editors from several global regional bureaus. Analysis using Network Gatekeeping Theory on the global environmental online media site Mongabay.com found that the editorial team plays a role in determining the direction of control over the information selected, added and presented regarding reporting on Indigenous 205 communities. The intrinsic narrative presented by this organization is based on knowledge at the individual level (founders, editors, journalists) about the topic, their belief in the values of diversity, relationships with Indigenous activists and human rights movement groups, and primary sources. information, and empirical experience of field coverage. This narrative is related to deepening the history of Indigenous peoples, the resources of how Indigenous peoples maintain their living spaces, areas with remaining forests that are rich in animal and plant diversity, mineral resources, coastal resources, and various potential environmental services. The emerging narrative of indigenous people's resistance to large capitalist groups is also a form of resistance to the capitalist-hegemonistic regime which is pro-market and pro-capital. Keywords: Climate change, Environmental communication, Digital media, Mass media, Network Gatekeeping Theory